# SOLVING PROBLEMS USING TRIGONOMETRIC FORMULAS

Problem 1 :

If x cos θ = y cos (θ + 2π/3) = z cos (θ + 4π/3), find the value of xy + yz + zx.

Solution :

Given that :

x cos θ = y cos (θ + 2π/3) = z cos (θ + 4π/3)

Note that xy + yz + zx = xyz(1/x + 1/y +1/z)

If we put x cos θ  =  y cos (θ+2π/3)  =  zcos(θ+4π/3) = k

Then

 x cos θ = kx=k/cos θ ycos(θ + 2π/3) = ky = k/cos(θ+ 2π/3) zcos(θ+4π/3) = kz =k/cos(θ+4π/3)

1/x  =  cos θ /k  ---(1)

1/y  =  cos(θ+ 2π/3)/k ---(2)

1/z  =  cos(θ+4π/3)/k  ---(3)

(1) + (2) + (3)

(1/x) + (1/y) + (1/z)  =

(1/k) [ cos θ + cos(θ+ 2π/3) + cos(θ+ 4π/3) ]

=  (1/k) [ cos θ + cos θ cos 2π/3 - sin θ sin 2π/3 + cos θ cos 4π/3 - sin θ sin 4π/3]

 cos (2π/3)  =  -1/2sin (2π/3)  =  √3/2 cos (4π/3)  = - 1/2sin (4π/3)  =  -√3/2

=  0

So, the value of xy + yz + zx is 0.

Problem 2 :

Prove that :

sin(A + B) sin(A − B)  =  sin2 A − sin2 B

Solution :

sin (A + B)  =  sin A cos B + cos A sin B

sin (A - B)  =  sin A cos B - cos A sin B

Then, sin (A + B) sin (A - B) :

=  (sin A cos B + cos A sin B)(sin A cos B - cos A sin B)

=  sin2A cos2B - sin A sin B cos A cos B + sin A sin B cos A cos B - cos2A sin2B

=  sin2A cos2B - cos2A sin2B

=  sin2A (1-sin2B) - (1-sin2A) sin2B

=  sin2A - sin2sin2B - sin2B + sin2A sin2B

=  sin2A - sin2B

Problem 3 :

Prove that :

cos(A + B) cos(A − B)  =  cos2 A − sin2 B = cos2 B − sin2 A

Solution :

cos(A + B)  =  cos A cos B - sin A sin B

cos(A - B)  =  cos A cos B + sin A sin B

Then, cos(A + B) cos(A - B) :

=  (cos A cos B - sin A sin B)(cos A cos B + sin A sin B)

=  (cos2 A cos2 B + cos A sin A cos B sin B - cos A sin A cos B sin B - sin2 A sin2 B

=  cos2 Acos2 B-sin2 A sin2 B -----(1)

From (1),

=  cos2 A(1-sin2 B)-(1 - cos2 A)sin2 B

=  cos2 A-cos2 Asin2 B - sin2 B + cos2 Asin2 B

=  cos2 A - sin2 B

From (1),

=  (1-sin2A) cos2 B-sin2 A (1-cos2 B)

=  cos2 B-sin2A cos2 B - sin2 A + sin2A cos2 B

=  cos2 B - sin2 A

Hence proved.

Problem 4 :

Prove that :

sin2(A + B) - sin2(A - B)  =  sin2Asin 2B

Solution :

From (i) we have

sin2 A − sin2 B  =  sin(A + B) sin(A − B) ----(1)

By comparing the given question with the formula, we get A  =  A + B and B  =  A - B

A + B  ==>  A + B + A - B  ==>  2A

A - B  ==>  A + B - (A - B) ==> 2B

Substitute 2A for (A + B) and 2B for (A - B) in (1).

(1)-----> sin2(A + B) − sin2(A − B)  =  sin2Asin 2B

Hence proved.

Problem 5 :

Prove that :

cos 8θ cos 2θ  =  cos2 5θ − sin2 3θ

Solution :

We may write 8θ as (5θ + 3θ) and 2θ as (5θ - 3θ).

Then,

cos 8θ cos 2θ  =  cos (5θ + 3θ) cos (5θ - 3θ)

From (ii), we have

cos(A + B) cos(A − B) = cos2 A − sin2 B

Then,

cos (5θ + 3θ) cos (5θ - 3θ)  =  cos2 5θ − sin2 3θ

Hence proved.

Apart from the stuff given above, if you need any other stuff in math, please use our google custom search here.

Kindly mail your feedback to v4formath@gmail.com

We always appreciate your feedback.

©All rights reserved. onlinemath4all.com

## Recent Articles

1. ### SAT Math Videos

May 22, 24 06:32 AM

SAT Math Videos (Part 1 - No Calculator)

Read More

2. ### Simplifying Algebraic Expressions with Fractional Coefficients

May 17, 24 08:12 AM

Simplifying Algebraic Expressions with Fractional Coefficients

Read More

3. ### The Mean Value Theorem Worksheet

May 14, 24 08:53 AM

The Mean Value Theorem Worksheet

Read More